2010
DOI: 10.1111/j.1469-7998.2010.00698.x
|View full text |Cite
|
Sign up to set email alerts
|

Inferring colonization history and dispersal patterns of a long‐lived seabird by combining genetic and empirical data

Abstract: Identifying biological trends and threats to organisms that make long distance migrations are often the limiting factors in their conservation. Indeed, Laysan albatross Phoebastria immutabilis are highly vagile seabirds, foraging throughout the North Pacific Ocean. Despite mark-recapture data indicating natal philopatry, Laysan albatross recently re-colonized several anthropogenically extirpated breeding locations. At the same time, a breeding population in the north-western Hawaiian Islands was lost to erosio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 33 publications
1
16
0
1
Order By: Relevance
“…A total of 322 Hawaiian petrel samples were obtained from across the current and historical breeding range of this species (Table 1, Figure 1). Modern samples (N¼294) consisting of blood, muscle or other tissue, bone and feather were salvaged from carcasses of birds depredated in breeding colonies on Hawaii, Maui, Lanai andKauai, between 1990 and2010, or collected from birds that were handled during conservation management procedures, such as rehabilitation following power-line strikes or crashes due to disorientation caused by artificial light sources (Podolsky et al, 1998). Crashed birds and carcasses were assumed to be breeders (or the offspring of breeders) on the island where they were discovered, as nonbreeders depart during the first half of chick-rearing (Simons, 1985;Simons and Hodges, 1998).…”
Section: Materials and Methods Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 322 Hawaiian petrel samples were obtained from across the current and historical breeding range of this species (Table 1, Figure 1). Modern samples (N¼294) consisting of blood, muscle or other tissue, bone and feather were salvaged from carcasses of birds depredated in breeding colonies on Hawaii, Maui, Lanai andKauai, between 1990 and2010, or collected from birds that were handled during conservation management procedures, such as rehabilitation following power-line strikes or crashes due to disorientation caused by artificial light sources (Podolsky et al, 1998). Crashed birds and carcasses were assumed to be breeders (or the offspring of breeders) on the island where they were discovered, as nonbreeders depart during the first half of chick-rearing (Simons, 1985;Simons and Hodges, 1998).…”
Section: Materials and Methods Samplesmentioning
confidence: 99%
“…If petrels are able to overcome isolating mechanisms and disperse prior to complete extirpation then this could explain why some species do not seem to exhibit population genetic differentiation, despite evidence of strong philopatry from mark-recapture studies. For example, the Laysan albatross is known to exhibit strong natal philopatry (Fisher, 1976), but very weak population structure was found in this species (Young, 2010). While density-dependent dispersal was suggested as one potential cause, displacement from several extirpated colonies could also lead to weak population structure.…”
Section: Population Extirpation and Gene Flowmentioning
confidence: 99%
“…(); 16 , Silva et al . (); 17 , Young (); 18 , Walsh & Edwards (); 19 , Techow, Ryan & O'Ryan (); 20 , Brown et al . (); 21 , Rayner et al .…”
Section: Approachmentioning
confidence: 99%
“…For example, Morris-Pocock et al (2008) found genetic structure in Atlantic Common Murres (Uria aalge) owing to historical fragmentation even with high contemporary gene flow. The limited population structure observed among Laysan Albatrosses (Phoebastria immutabilis) is likely a result of both historical and current gene flow, because the birds started recolonising many anthropogenically extirpated breeding sites in the 1970s (Young 2010).…”
Section: Contemporary Gene Flow or Historical Connectivity?mentioning
confidence: 99%